Consumer perception of sustainable practices in dairy production - Simona Naspetti; Serena Mandolesi; Jeroen Buysse; Terhi Latvala; Phillipa Nicholas; Susanne Padel; Ellen J. Van Loo; Raffaele Zanoli (Agricultural and Food Economics, 2021)
Home-grown protein crops as an alternative to soya in dairy cattle meals, as well as other sustainable ethical-based practices, have been proposed to increase the sustainability of dairy production. Data on consumer acceptance of the three novel sustainable production strategies of 'agroforestry', 'prolonged maternal feeding' of young cattle and 'alternative protein source' were collected through an online survey on consumer in six European Union countries: Austria, Belgium, Denmark, Finland, Italy and the UK. Using Chen's extended version of the Theory of Planned Behaviour model, the underlying model hypotheses on the attitudes and intentions of these consumers towards these production practices were tested, to establish the explanatory power of the model in the specific context of novel sustainable production strategies. Furthermore, the influence of gender and consumer ethical choices on their attitudes towards these innovative practices was also tested. These data show that 'prolonged maternal feeding' is the novel production practice that has the highest level of acceptance by consumers in all of these countries, with the least accepted practice as 'alternative protein source'. Unexpectedly, increased availability of home-grown feed, which is grounded on both farmer and societal interests for higher input self-sufficiency and more sustainable production practices, was little appreciated by consumers, although their intentions appear to be dependent on their moral norms.
Keywords: 330; Sustainable dairy farming; Animal welfare; Alternative feed; Organic and low-input farming